Penerapan Pembelajaran Berbasis Proyek Nyata untuk SDGs Melalui Kemitraan Multipihak di SMP Negeri 1 Sungkai Tengah - Dwi Retno Wati (CV. ITTC INDONESIA, 2026)
Education for Sustainable Development Goals (SDGs) requires learning approaches that are applicable and relevant to local contexts. This study examines the implementation of a real project-based learning model through multi-stakeholder partnerships at SMP Negeri 1 Sungkai Tengah, North Lampung. Using a descriptive qualitative approach, the research involved teachers and eighth-grade students in three main projects: (1) agricultural land management for food crops with the community, (2) honey bee cultivation with CV Bramara Sentosa, and (3) oyster mushroom cultivation using corn cob waste media with village MSMEs. The results indicate that real project-based learning enhances students' understanding of SDG principles, particularly Goals 2, 8, 12, and 15, while developing responsibility, ecological awareness, and collaborative skills. The study reveals key supporting factors such as shared vision and reciprocal benefits, as well as challenges like time constraints and differing work cultures, which were successfully managed through adaptive communication and structured agreements. Authentic assessment methods, including portfolios and presentations to community panels, proved effective in measuring holistic competency development. The study concludes that school-community-business synergy is an effective strategy for transformative SDG learning at the junior high school level.